2006
DOI: 10.1542/peds.2005-1634
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to and Effectiveness of Positive Airway Pressure Therapy in Children With Obstructive Sleep Apnea

Abstract: OBJECTIVES. Positive airway pressure therapy (PAP) is frequently used to treat children who have obstructive sleep apnea syndrome and do not respond to adenotonsillectomy. However, no studies have evaluated objectively adherence to PAP in children, and few studies have evaluated objectively the effectiveness of PAP. The objective of this study was to determine adherence and effectiveness of PAP (both continuous [CPAP] and bilevel [BPAP] pressure) in children with obstructive apnea.METHODS. A prospective, mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
242
4
17

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 382 publications
(280 citation statements)
references
References 33 publications
15
242
4
17
Order By: Relevance
“…1 Adverse outcomes associated with pediatric OSA include neurobehavioral, cardiovascular, metabolic, and growth abnormalities, which contribute to decreased social functioning and quality of life; successful and consistent treatment is associated with reduction of morbidity, including improvement of daytime symptoms and neurobehavioral parameters. [2][3][4][5][6][7] First-line therapy for children entails optimization of airway patency by adenotonsillectomy (AT). 1 Overall surgical intervention is successful in 79% of patients, however those with severe OSA, obesity, and additional risk factors, such as genetic syndromes are less likely to be cured by AT alone.…”
Section: Introductionmentioning
confidence: 99%
“…1 Adverse outcomes associated with pediatric OSA include neurobehavioral, cardiovascular, metabolic, and growth abnormalities, which contribute to decreased social functioning and quality of life; successful and consistent treatment is associated with reduction of morbidity, including improvement of daytime symptoms and neurobehavioral parameters. [2][3][4][5][6][7] First-line therapy for children entails optimization of airway patency by adenotonsillectomy (AT). 1 Overall surgical intervention is successful in 79% of patients, however those with severe OSA, obesity, and additional risk factors, such as genetic syndromes are less likely to be cured by AT alone.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] CPAP adherence patterns of adolescents have not been extensively studied, but studies of medication adherence in other adolescent groups, such as asthmatics, epileptics, and diabetics have demonstrated poor adherence. 13,14 Poor adherence in adolescents may be related to not understanding or not perceiving the benefi ts of the treatment, wanting to conform to peers, and rebelling against authority.…”
mentioning
confidence: 99%
“…Although the overall PAP adherence in our sample was very low, it was similar to other pediatric centers. [7][8][9] The observed high risk for poor adherence to PAP therapy confirms why the American Academy of Pediatrics clinical practice guideline for evaluation and management of OSA in children does not recommend PAP therapy as a reliable first-line therapy for OSA in children when adenotonsillectomy is an option. 1 In addition, we also observed that adherence for the whole group declined with time.…”
Section: Discussionmentioning
confidence: 99%
“…1 PAP is a very effective therapy, but poor adherence to therapy is a limiting factor, with most studies showing a high dropout rates in up to one-third of children and low average nightly use, often less than one-half of their expected sleep period for age. [7][8][9] Usage of the device can be uncomfortable for children, disruptive to the family lifestyle, and requires parental supervision and support. Recent studies have shown better neurobehavioral outcomes in children who are adherent to PAP therapy.…”
Section: Introductionmentioning
confidence: 99%